Successful treatment of Keratitis caused by Mycobacterium chelonae and an overview of previous cases in Europe - Kukla, Rudolf; Nouzovska, Katerina; Ryskova, Lenka; Rozsivalova, Petra; Pavlik, Ivo; Bostik, Pavel (Annals of clinical microbiology and antimicrobials, 2024)
INTRODUCTION AND PURPOSE: Mycobacterium (M.) chelonae is responsible for a half of relatively rare nontuberculous mycobacteria (NTM) keratitis. We report a case of M. chelonae keratitis in a woman following sclerocorneal suture extraction after cataract surgery. RESULTS: A 70-year-old woman presented with a red eye and corneal infiltration of her left eye six weeks following sclerocorneal suture extraction after an elective cataract surgery in another institute. She complained of a sharp, cutting pain and photophobia. Since initial corneal scrapes and conjunctival swabs proved no pathogen using culture and PCR methods, non-specific antibiotics and antifungal agents were administered. As keratitis was complicated by an inflammation in the anterior chamber and vitreous, samples of the vitreous fluid were sent for microbiologic examination. DNA of Epstein-Barr virus (EBV) was repeatedly detected. Since the intrastromal abscess had formed, corneal re-scrapings were performed and M. chelonae was detected using culture, MALDI-TOF MS and PCR methods. Therapy was changed to a combination of oral and topical clarithromycin, intravitreal, topical and intracameral amikacin, and oral and topical moxifloxacin. The successful therapy led to stabilization. The optical penetrating keratoplasty was performed and no signs of the infection recurrence were found. CONCLUSIONS: The diagnosis of nontuberculous mycobacterial keratitis is difficult and often delayed. An aggressive and prolonged antimicrobial therapy should include systemic and topical antibiotics. Surgical intervention in the form of corneal transplantation may be required in the active and nonresponsive infection. In the presented case this was necessary for visual rehabilitation due to scarring.
Keywords: Aged; Evropa; výsledek terapie; moxifloxacin; Keratitis; antibakteriální látky; lidé; senioři; ženské pohlaví; Fluoroquinolones; amikacin; fluorochinolony; Female; Europe; keratitida; Clarithromycin; klarithromycin; Amikacin; Treatment Outcome; Anti-Bacterial Agents; Mycobacterium Infections, Nontuberculous; Humans; Moxifloxacin; atypické mykobakteriální infekce; Mycobacterium chelonae